Investigate The Incidence Of Bacterial Streptococcus Pyogenes And Klebsiellae Pneumoniae In COVID-19 Patients By Direct Detection (Journal of Pharmaceutical Negative Results, 2022)
This study is conducted on patients infected with COVID19 Those who are hospitalized in intensive care units in to AL-Shifa Center at AL-Zahraa Teaching Hospital for the period from December 2021 to March 2021, for age groups (41-80 years) and of both sexes. As 50 swabs samples are collected two swabs for each patient one for culture and other for PCR after direct extraction for DNA, in order to investigate S. pyogen and K. pneumoniae infections associated with the emerging corona virus. During the laboratory diagnosis, culturing was obtained 21 (42%) positive samples for S. pyogen and 5 (10%) for K. pneumoniae. The extent of resistance of some commonly used antibiotics against S. pyogen and K. pneumoniae was 8 antibiotic disk for each all.PCR detection for 50 patients after extraction for swab gave positive result for S. pyogen 5 (10%) and K. pnemonaie 7(14%). Compared to those without additional pathogens, patients with co-infections and/or secondary infections were more likely to receive antibiotics.